Joining of Ti6Al4V to Al2O3 Using Nanomultilayers - Silva Jr., Marcionilo (2022)
Diffusion bonding of Ti6Al4V to Al2O3 using Ni/Ti reactive nanomultilayers as interlayer material was investigated. For this purpose, Ni/Ti multilayer thin films with 12, 25, and 60 nm modulation periods (bilayer thickness) were deposited by d.c. magnetron sputtering onto the base materials’ surface. The joints were processed at 750 and 800 ◦C with a dwell time of 60 min and under a pressure of 5 MPa. Microstructural characterization of the interfaces was conducted by scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDS), and electron backscatter diffraction (EBSD). The mechanical characterization of the joints was performed by nanoindentation, and hardness and reduced Young’s modulus distribution maps were obtained across the interfaces. The joints processed at 800 ◦C using the three modulation periods were successful, showing the feasibility of using these nanolayered films to improve the diffusion bonding of dissimilar materials. Using modulation periods of 25 and 60 nm, it was also possible to reduce the bonding temperature to 750 ◦C and obtain a sound interface. The interfaces are mainly composed of NiTi and NiTi2 phases. The nanoindentation experiments revealed that the hardness and reduced Young’s modulus at the interfaces reflect the observed microstructure.